COMMUNITY ASSISTANCE IN COMMUNICATION SKILLS DEVELOPMENT TRAINING PROGRAMS - Putrie, Rena Augia; Asfahani, Asfahani; Rima Harati; Ratna Ayu Pawestri Kusuma Dewi (Community Development Journal : Jurnal Pengabdian Masyarakat, 2024)
Effective communication skills are essential for personal development and community cohesion, yet many communities need access to tailored training programs. The Community Assistance aims to address this gap by enhancing the communication abilities of community members through a participatory and context-specific approach. The program was designed to improve public speaking, active listening, non-verbal communication, and written communication skills among participants. Utilizing a Participatory Action Research (PAR) methodology, the program engaged community members in the needs assessment, design, implementation, and evaluation phases. This collaborative approach ensured the training was relevant and effective. The results demonstrated significant improvements in participants' communication skills, with notable increases in confidence and proficiency. Enhanced communication led to greater community engagement, improved employment prospects, and better educational outcomes. The training also strengthened social networks and fostered a sense of community cohesion. In conclusion, the program successfully empowered individuals and promoted sustainable community development. The findings underscore the importance of tailored communication skills training and provide a model for similar initiatives in other communities.